The Profile of a Child with Development Disorders in a Mass-School Teachers' View - Hanna Żuraw (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Analysing social attitudes is necessary in a situation of total educational integration of disabled children into mass school. The article presents the results of research into stereotypes of children with abnormalities in development. Theoretical basis of my resolving are derived from social psychology and sociology. Teacher's opinions were analysed according to the Bogardus idea and to the semantic meaning of words. Biological determinism, stereotypes are still present in the concept of this group. "Everywhere but not with me in my leisure time, not in my home". In official declaration we observe a conventional sympathy, whereas the in area of behavior we perceive distance and anxiety. Why? Because health is still one of the most important values. Disability is not wanted. This tendency is still actual. Additional factor which leads to dislike of children with disability is present organisation of education which does not provide an effective support for teachers and pupils.